Immune‐related alopecia (areata and universalis) in cancer patients receiving immune checkpoint inhibitors. (1st June 2017) - Zarbo, A.; Belum, V.R.; Sibaud, V.; Oudard, S.; Postow, M.A.; Hsieh, J.J.; Motzer, R.J.; Busam, K.J.; Lacouture, M.E.
Summary: Cytotoxic T‐lymphocyte‐associated protein‐4, programmed cell death protein and programmed cell death protein ligand 1 monoclonal antibodies (immune checkpoint inhibitors), are used to treat various malignancies. Their mechanism of action involves the inhibition of negative regulators of immune activation, resulting in immune‐related adverse events (irAEs) including endocrinopathies, pneumonitis, colitis, hepatitis and dermatological events. Dermatological irAEs include maculopapular rash, pruritus, vitiligo, blistering disorders, mucocutaneous lichenoid eruptions, rosacea and the exacerbation of psoriasis. Alopecia secondary to immune checkpoint inhibitors has been reported in 1·0–2·0% of treated patients. Our objective is to characterize for the first time the clinicopathology of patients with alopecia areata (AA) secondary to immune checkpoint inhibitors, including the first report of anti‐PD‐L1 therapy‐induced AA, and review of the literature. Four cases of patients who developed partial or complete alopecia during treatment with immune checkpoint inhibitors for underlying cancer were identified from our clinics. Methods include the review of the history and clinicopathologic features. Three patients (75%) had AA and one had universalis. Two patients had a resolution after topical, oral or intralesional therapies and one had a resolution after immunotherapy was discontinued; all regrown hair exhibited poliosis. One of the four patients had coincident onychodystrophy. This report describes a series of four patients who developed partial or complete alopecia (i.e. areata and universalis) during treatment with immune checkpoint inhibitor therapies for cancer. The recognition and management of hair‐related irAEs are important for pretherapy counselling and interventions that contribute to maintaining optimal health‐related quality of life in patients.